The relation between egg quality and tenderness of baked custards - Yanke, Hannah C., author; Brown, Elfriede F., advisor; Allison, Inga M. K., committee member; Pyke, W. E. (Wesley Emerson), 1896-, committee member; Guard, Harris T., committee member; Avery, George T., committee member; Kezer, Alvin, 1877-, committee member; Durrell, L. W. (Lawrence Wood), 1888-, committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Eggs; Cooking (Eggs)